2023
DOI: 10.1038/s41392-022-01285-4
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome biogenesis in disease: new players and therapeutic targets

Abstract: The ribosome is a multi-unit complex that translates mRNA into protein. Ribosome biogenesis is the process that generates ribosomes and plays an essential role in cell proliferation, differentiation, apoptosis, development, and transformation. The mTORC1, Myc, and noncoding RNA signaling pathways are the primary mediators that work jointly with RNA polymerases and ribosome proteins to control ribosome biogenesis and protein synthesis. Activation of mTORC1 is required for normal fetal growth and development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 316 publications
2
39
0
Order By: Relevance
“…In current works on ribosomal proteins, their other functions beyond the framework of ribosome formation and maintenance are emphasized, e.g. activation of p53-dependent pathway in response to stress [26,27]. Thus, the significance of the longest intron feature of these genes highlighted by us may also turn out to be broader and awaits further investigation.…”
Section: Discussionmentioning
confidence: 97%

The longest intron rule

Dvorak,
Hlavac,
Hanicinec
et al. 2023
Preprint
“…In current works on ribosomal proteins, their other functions beyond the framework of ribosome formation and maintenance are emphasized, e.g. activation of p53-dependent pathway in response to stress [26,27]. Thus, the significance of the longest intron feature of these genes highlighted by us may also turn out to be broader and awaits further investigation.…”
Section: Discussionmentioning
confidence: 97%

The longest intron rule

Dvorak,
Hlavac,
Hanicinec
et al. 2023
Preprint
“…using mRNA as a template, and using amino acids as raw materials to synthesize proteins, is the ribosome's primary function (24). Previous studies have showed that the ribosome has a great deal of functions, including affecting protein synthesis and taking a signi cant role in cell differentiation, proliferation, transformation and apoptosis (25). VTE may be diagnosed and treated by using ribosomal protein family genes(26).…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal biogenesis, translation, and defects in the function of a single RP (including mutations in RP) have been associated with a variety of human congenital diseases called ribosomal diseases. [16][17][18] Studies have shown that ribosomal protein families regulate the expression of oncogenes and tumor suppressor genes, regulate cell cycle and apoptosis, promote angiogenesis, cooperate with chromosome genes to play a more extensive role, and regulate tumor proliferation, infiltration, metastasis and other malignant biological behaviors. [19] Figure 7.…”
Section: Discussionmentioning
confidence: 99%